Analysis of Feasibility Study of Construction and Operation of Special Terminals PT. Nan Indah Mutiara Shipyard - Desny Natal Ria; Usmanul Hayadi Umar (LEADER: Civil Engineering and Architecture Journal, 2023)
Shipping activities are divided into two types, namely commercial shipping and non-commercial shipping. One of the factors supporting naval facilities is needed infrastructure, namely ports. Port is one of the stops or terminals of ships after sailing and various kinds of activities such as the ups and downs of passenger departures, loading and unloading goods, refueling or ship rests at the port, and so on. To support its own business activities, the construction of a Special Terminal can be built which includes a regional review of population, employment, regional income, transportation, geographical location of Batam City, climate, government, regional infrastructure, and natural resource potential carried out and coordinated with the government on the analysis of feasibility studies for the construction and operation of special terminals that require a special operating permit specifically good and feasible on land or in sea or waters with K3 (Occupational Health and Safety). The feasibility study of Tersus includes, among others, the plan for the volume of loading and unloading raw materials, supporting equipment, and the frequency of ship visits, safety and security aspects of shipping at special terminals and survey results regarding tides, currents, bathimetric depth, with detailed situations at the location of special terminal construction points and environmental aspects of water quality management efforts, population decline and biota diversity, air and noise quality, shipping safety, as well as employment opportunities and efforts to obtain special terminal operating permits require increasing the level of special terminal services at PT. Nanindah Pearl Shipyard.